Habitat and Distribution of Desmopuntius gemellus (Kottelat, 1998) at Palm Oil Plantation Canal Near Pidada River, Tulang Bawang, Lampung - Ferry Tito Wijaya; Indra Gumay Yudha; Rara Diantari (Jurusan Perikanan dan Kelautan, 2021)
Desmopuntius gemellus is a native species of peat swamp waters in Southeast Asia. This fish is economically important value for the local community, for example as consumption fish and as bait to catch carnivorous fish. Until now there has been no management effort to protect the sustainability of the fish. Ecobiology studies are needed as initial information in managing this fish. Samples were collected from primary and secondary canal stations at the palm oil plantation in Penawartama District, Tulang Bawang Regency during October 2019 to January 2020. A total of 1,088 fish samples were collected by using lift net, with the most distribution in the secondary canal. Main component analysis shows that secondary canal stations are more characterized by temperature parameters. And the primary canal is characterized by depth, brightness, current, and dissolved oxygen.